PSYCHOLOGICAL INTERVENTION WITH CHILDREN OF SEPARATED PARENTS: EXPERIENCE OF A FAMILY MEETING POINT - Orgilés Amorós, Mireia; Espada, José Pedro; Piñero, Jessica (Anales de Psicología / Annals of Psychology, 2007)
The goal of this work is to examine the functioning of a Family Meeting Point and presenting a descriptive study of their users. A Family Meeting Point is a neutral resource for the families that in their process of divorce require technical and institutional support. It facilitates the relation between the children and the non-custodial father. Psychologists and educators provide a temporary intervention re-establishing the relation between the child and the non-custodial father. The sample of the study is composed of 71 cases registered for 12 months. The sample has the fol-lowing characteristics: light predominance of boys and range of age from 6 months to 12 years. The most common psychological problems in chil-dren are examined. The observation of the children behaviour shows an improvement in their relation with the non-custodial father since they come to the Family Meeting Point, as well as a minor conflict between both parents. The high number of cases in the Family Meeting Point and the benefits observed in the well-being of children support the need for this type of services.